Does postoperative delirium following elective noncardiac surgery predict long-term mortality? - Ziman, Nathan (Age Ageing, 2020)
OBJECTIVE: to determine whether incident postoperative delirium in elective older surgical patient was associated with increased risk for mortality, controlling for covariates of 5-year mortality. DESIGN: secondary analysis of prospective cohort studies. SETTING: academic Medical Center. SUBJECTS: patients ≥65 years of age undergoing elective non-cardiac surgery. OUTCOMES: postoperative assessments of delirium measured using the Confusion Assessment Method (CAM), mortality within 5 years of the index surgery was determined from National Death Index records. RESULTS: postoperative delirium occurred in 332/1,315 patients (25%). Five years after surgery, 175 patients (13.3%) were deceased. Older age was associated with an increased odds of mortality [odds ratio (OR) 1.90, 95% confidence interval (CI) 1.20–2.70] for those aged 70–79 years compared to those aged <70 years, and OR 3.29, 95% CI 2.14–5.06 for those aged >80 years. Other variables associated with 5-year mortality on bi-variate analyses were white race, self-rated functional status, lower preoperative cognitive status, higher risk score as measured by the American Society of Anesthesiologists (ASA) classification, higher surgical risk score, history of congestive heart failure, myocardial infarction, renal disease, cancer, peripheral vascular disease and postoperative delirium. However, postoperative delirium was not associated with 5-year mortality on multi-variate logistic regression (OR 1.18, 95% CI 0.85–1.65). CONCLUSIONS: our results showed that delirium was not associated with 5-year mortality in elective surgical patients after consideration of co-variates of mortality. Our results suggest the importance of accounting for known preoperative risks for mortality when investigating the relationship between delirium and long-term mortality.